KONSEP KHILAFAH DALAM PANDANGAN SYEKH TAQIYUDDIN AN-NABHANI - Indah,; Hasan, Hamzah; Aisyah, Nur (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar'iyyah, 2024)
This research aims to describe the caliphate government system in the view of Sheikh Taqiyuddin an-Nabhani and the relationship between religion and the caliphate state in the view of Sheikh Taqiyuddin an-Nabhani. And the ideal state form according to Sheikh Taqiyuddin an-Nabhani. In answering the problem, the author uses the fiqh siyasah approach as for the method of collecting secondary data in the form of primary material, secondary is done by reading literature, scientific works, research results, documents or books related to research. The results of the research show that the Islamic government system in the view of Sheikh Taqiyuddin An-Nabhani consists of four pillars, namely sovereignty in the hands of syara', power belonging to the people, appointing a caliph whose law is obligatory for all Muslims, only the caliph has the right to do tabbani (adoption) against syara law '. The relationship between religion and the state according to Sheikh Taqiyuddin An-Nabhani is to preserve religion, organize community affairs, protect the country and the people, spread the message of Islam, eliminate opposition and disagreements between communities. The ideal form of government according to Sheikh Taqiyuddin An-Nabhani from the aspect of the form that describes the existence of the country, as well as the things that make it completely different from the form of government that exists in the world. Includes non-monarchical Islamic governments, non-republican Islamic governments, non-imperial Islamic governments, and non-federal Islamic governments.